рН-зависимый структурный переход в гомопурин-гомопиримидиновом блоке в сверхспиральной ДНК - Лямичев, В.И.; Миркин, С.М.; Франк-Каменецкий, М.Д. (Биополимеры и клетка, 1986)
С помощью двумерного электрофореза обнаружен структурный переход нового типа в гомопурин-гомопиримидиновом участке в сверхспиральной ДНК. В отличие от других исследованных переходов, этот переход сильно зависит от рН, что проявляется в уменьшении плотности отрицательной сверхспирализации, необходимой для структурного изменения, при уменьшении рН. Новая структура ДНК названа Н-формой. За допомогою двовимірного електрофорезу виявлено структурний перехід нового типу в гомопурин-гомопіримідиновій ділянці в надспіральній ДНК. На відміну від інших досліджених переходів, цей перехід сильно залежить від рН, що проявляється у зменшенні щільності негативної надспіралізаціі, необхідної для структурної зміни, при зниженні рН. Нова структура ДНК названа Н-формою. The 509-bp-long fragment of sea urchin P. miliaris histone gene spacer region was inserted into plasmid pUC19. The fragment contains the 60-bp-long homopurine-homopyrimidine tract that is known to be hypersensitive to the S1 endonuclease. Two-dimensional gel electrophoresis has permitted revealing a sharp structural transition in the insert with an increase in DNA superhelicity. As in the cases of cruciform and Z-form formation, the observed transition partially relaxes the superhelical stress. In contrast with the other two well documented transitions, the observed transition strongly depends on pH. At pH 7.0 and above the transition occurs at negative superhelicities which exceed the physiological range (– σ > 0.08) by the absolute value. For pH 6.0 the transition occurs at – σ = 0.055, whereas for pH 4.3 it takes place at – σ = 0.001. A comprehensive analysis of the data obtained has made it possible to define the nature of the observed transition. It is concluded that under the action of superhelical stress or/and at the low pH values the homopurine-homopyrimidine tracts form a novel spatial structure of DNA called the H-form.